Kolaboratif Learning sebagai Strategi Penguatan Literasi Digital pada Peserta Didik Sekolah Dasar - Muhammad Alwan; Nailatul Alawiyah (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
This study examines the effectiveness of implementing Collaborative Learning as a strategy to strengthen Literasi digital among elementary school students, emerging as a response to challenges related to students’ limited ability to access, understand, and utilize digital information critically and responsibly. The main problem addressed in this research concerns the lack of learning models capable of integrating cooperation, creativity, and critical thinking skills with digital competencies relevant to 21st-century demands. Employing a descriptive qualitative method supported by a literature review, the data were collected from various scientific sources such as books, journals, articles, and previous studies. The findings indicate that Collaborative Learning effectively enhances students’ Literasi digital skills through activities emphasizing interaction, discussion, problem-solving, and the use of digital platforms such as Google Classroom, Canva, Kahoot, and Padlet. The teacher’s role as a facilitator is crucial in creating an active, adaptive, and student-centered learning environment. Challenges such as limited devices and internet access still arise, yet these can be mitigated through teacher competency development, parental support, and the optimal use of accessible digital resources. The study concludes that integrating Collaborative Learning with Literasi digital not only improves academic competence but also fosters a learning ecosystem that is engaging, participatory, and aligned with technological advancements. The novelty of this research lies in highlighting that student collaboration, when combined with appropriate technological integration, can serve as an effective strategy for strengthening Literasi digital sustainably at the elementary school level.